2011
DOI: 10.1007/s00455-010-9323-z
|View full text |Cite
|
Sign up to set email alerts
|

Normal Swallowing Acoustics Across Age, Gender, Bolus Viscosity, and Bolus Volume

Abstract: Cervical auscultation has been proposed as an augmentative procedure for the subjective clinical swallowing examination due to the tangible differences between normal and dysphagic swallowing sounds. However, the research is incomplete regarding cervical auscultation and swallowing acoustics in that the differences between the sounds of normal versus dysphagic swallowing have yet to be fully understood or quantified. The swallows of 96 reportedly healthy adults, balanced for gender and divided into younger, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 22 publications
7
36
1
2
Order By: Relevance
“…The results showed that the swallowing time was longer in the group of elderly. In addition, the peak intensity was also more intense and the signal peak frequency was more acute in the group of the elderly, showing that an increased time in the pharyngeal phase occurs parallel to the increase of age 11 . Another study analyzed the duration of swallowing sounds in healthy subjects, 20 males and 10 females (age 37 ± 11).…”
Section: Correspondence Of Swallowing Sounds With Physiological Eventsmentioning
confidence: 84%
See 3 more Smart Citations
“…The results showed that the swallowing time was longer in the group of elderly. In addition, the peak intensity was also more intense and the signal peak frequency was more acute in the group of the elderly, showing that an increased time in the pharyngeal phase occurs parallel to the increase of age 11 . Another study analyzed the duration of swallowing sounds in healthy subjects, 20 males and 10 females (age 37 ± 11).…”
Section: Correspondence Of Swallowing Sounds With Physiological Eventsmentioning
confidence: 84%
“…Thus, it is evident an increasing number of studies with the purpose of studying the swallowing sounds and its correspondence with other physiological events in healthy subjects 9,11,[25][26][27] . The latter, relating the cervical auscultation findings with other assessment methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first analysis method is the most simplistic and extracts the most basic features and conclusions from the time domain recordings. For example, researchers have matched certain visual landmarks of a raw cervical auscultation signal with some specific physiological events [19], [37], [48], [69], [103], determined the onset and duration of a swallow [34], [68], [69], [94], [95], [97], [101], [110], [113], [114], or simply counted the number of swallows that occurred over a certain period [40], [95], [102], [104], [107], [111]. The second analysis method also uses simple features of the signal, but uses the subjective opinion of a trained expert listening to the acoustic signal rather than the researcher’s visual analysis of the signal waveform.…”
Section: Signal Analysismentioning
confidence: 99%